A PID parameter tuning method for air conditioning system based on annealing genetic algorithm. (1st January 2014) - Nie, Jianbin; Zhou, Yuting; Chen, Chen; Han, Ning; Li, Deying
In view of the characteristics of central air conditioning control system (with great inertia and multiple disturbances) and the prematurity of conventional genetic algorithm, this paper integrated simulated annealing algorithm into conventional genetic algorithm to realise the proportional, integral, differential (PID) parameter tuning. Local optimal solution was effectively rejected by stretching fitness function and introducing access criterion with controlled probability. MATLAB simulation results showed that the system response lagged only 1000 s, and the efficiency was improved by 80% by using this method. In addition, the fitness value was smaller than that of conventional genetic algorithm.